2019
DOI: 10.1111/jth.14460
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemophilia A caused by an unbalanced chromosomal rearrangement identified using nanopore sequencing

Abstract: Background:No F8 genetic abnormality is detected in about 2% of severe hemophilia A patients using conventional genetic approaches. In these patients, deep intronic variation or F8 disrupting genomic rearrangement could be causal.Objective: To characterize, in a genetically unresolved severe hemophilia A patient, a new Xq28 rearrangement disrupting F8 using comprehensive molecular techniques including nanopore sequencing. Results: Long-range polymerase chain reaction (PCR) performed throughout F8 identified a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A similar molecular mechanism occurs for inv1 6,9 . The remaining cases of F8 structural variants result from non‐recurrent molecular mechanisms 10–13 …”
Section: Introductionmentioning
confidence: 69%
“…A similar molecular mechanism occurs for inv1 6,9 . The remaining cases of F8 structural variants result from non‐recurrent molecular mechanisms 10–13 …”
Section: Introductionmentioning
confidence: 69%
“…For example, ONT sequencing of human genomes revealed that an expansion of tandem repeats in the ABCA7 gene was associated with an increased risk of Alzheimer's disease 207 . ONT sequencing was also used to discover a new 3.8-Mb duplication in the intronic region of the F8 gene in an individual with hemophilia A 208 . Other examples cover a large range of diseases and conditions, including autism spectrum disorder 209 , Temple syndrome 210 , congenital abnormalities 112 , glycogen storage disease type Ia (ref.…”
Section: Identifying Large Svsmentioning
confidence: 99%
“…Long-read sequencing is becoming increasingly used in clinical research 58 . Advantages over short-read methods have been noted for applications such as identifying SVs 28,59 , resolving complex SVs 29 , phasing alleles 60 , sequencing repetitive or highly homologous regions 61 and inferring methylation state 30 . The fast turn-around time of Nanopore sequencing in particular has already led to the development of rapid diagnostic assays for specific cancers 30,31 .…”
Section: Discussionmentioning
confidence: 99%